Interazioni tra Glicoproteine che mediano la penetrazione del Virus Herpes Simplex nella cellula e disegno razionale di Peptidi Inibitori - Amasio, Michele <1979> (Alma Mater Studiorum - Università di Bologna, 2009)
Herpes simplex virus entry into cells requires a multipartite fusion apparatus made of gD, gB and heterodimer gH/gL. gD serves as receptor-binding glycoprotein and trigger of fusion; its ectodomain is organized in a N-terminal domain carrying the receptor-binding sites, and a C-terminal domain carrying the profusion domain, required for fusion but not receptor-binding. gB and gH/gL execute fusion. To understand how the four glycoproteins cross-talk to each other we searched for biochemical defined complexes in infected and transfected cells, and in virions. We report that gD formed complexes with gB in absence of gH/gL, and with gH/gL in absence of gB. Complexes with similar composition were formed in infected and transfected cells. They were also present in virions prior to entry, and did not increase at virus fusion with cell. A panel of gD mutants enabled the preliminary location of part of the binding site in gD to gB to the aa 240-260 portion and downstream, with T306P307 as critical residues, and of the binding site to gH/gL at aa 260-310 portion, with P291P292 as critical residues. The results indicate that gD carries composite independent binding sites for gB and gH/gL, both of which partly located in the profusion domain. The second part of the project dealt with rational design of peptides inhibiting virus entry has been performed. Considering gB and gD, the crystal structure is known, so we designed peptides that dock in the structure or prevent the adoption of the final conformation of target molecule. Considering the other glycoproteins, of which the structure is not known, peptide libraries were analyzed. Among several peptides, some were identified as active, designed on glycoprotein B. Two of them were further analyzed. We identified peptide residues fundamental for the inhibiting activity, suggesting a possible mechanism of action. Furthermore, changing the flexibility of peptides, an increased activity was observed,with an EC50 under 10μM. New approaches will try to demonstrate the direct interaction between these peptides and the target glycoprotein B.